Facile Synthesis of Copper‐Based Metal Oxide Nanoparticles with Exceptional Catalytic Activity for the Selective Oxidation of Styrenes into Benzaldehydes. Issue 3 (24th October 2014) - Ge, Danhua; Wang, Jiaqing; Geng, Hongbo; Lu, Shuanglong; Wang, Dongtao; Li, Xinming; Zhao, Xianli; Cao, Xueqin; Gu, Hongwei
Abstract The development of highly efficient catalysts for the selective oxidation of styrene to benzaldehyde has attracted great attention in recent years because of its significance in synthetic chemistry. In this study, two different kinds of copper‐based metal oxide nanoparticles (NPs), namely, CuO and CuO/Co3O4 NPs, were synthesized by a simple and scalable method, and these nanoparticles demonstrated efficient catalytic abilities for the selective oxidation of styrene and its derivatives to the corresponding aldehydes in the presence of tert‐butyl hydroperoxide (TBHP) under mild reaction conditions in excellent yields. Importantly, both of the heterogeneous catalysts can be recycled up to five runs while still maintaining their high catalytic activity.